2022
DOI: 10.3390/w14132121
|View full text |Cite
|
Sign up to set email alerts
|

Rainwater Isotopic Composition in the Ecuadorian Andes and Amazon Reflects Cross-Equatorial Flow Seasonality

Abstract: The variability of the rainfall stable isotopic values (δ2Hp, δ18Op) in the Ecuadorian Amazon to the Andes presents a marked local “altitude” effect. At the same time, this complex orography creates diverse precipitation regimes (unimodal, bimodal, and three-modal) that make it difficult to establish a relationship with the local amount. Nevertheless, stations along these regions show a similar intra-annual isotopic variability, with lower values during MAM and ON. In contrast, higher values are found during D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 80 publications
3
1
0
Order By: Relevance
“…The results presented here are also consistent with the work of Vargas et al. (2022) who found that the isotopic composition of rainfall in the Ecuadorian Andes is more related to regional precipitation amount than local rainfall, and that decreasing temperatures become the primary driver of isotopic changes during water vapor ascent within the Andes.…”
Section: δ18o‐tropical Climate Relationshipssupporting
confidence: 92%
See 1 more Smart Citation
“…The results presented here are also consistent with the work of Vargas et al. (2022) who found that the isotopic composition of rainfall in the Ecuadorian Andes is more related to regional precipitation amount than local rainfall, and that decreasing temperatures become the primary driver of isotopic changes during water vapor ascent within the Andes.…”
Section: δ18o‐tropical Climate Relationshipssupporting
confidence: 92%
“…This would be consistent with the interpretations of δ 18 O as a temperature recorder in polar ice cores (e.g., Andersen et al, 2004;Johnsen et al, 1995;Lorius et al, 1985;Rasmussen et al, 2013;Watanabe et al, 1999). The results presented here are also consistent with the work of Vargas et al (2022) who found that the isotopic composition of rainfall in the Ecuadorian Andes is more related to regional precipitation amount than local rainfall, and that decreasing temperatures become the primary driver of isotopic changes during water vapor ascent within the Andes.…”
Section: δ 18 O-tropical Climate Relationshipssupporting
confidence: 92%
“…For example, Aggarwal et al (2016) determined the stratiform fraction for a box of about 275 km x 275 km, whereas in our study, it is calculated for each grid cell (1.5 km x 1.5 km). In fact, we achieved the highest R 2 using a region-wide stratiform fraction (not shown) and similarly, Vargas et al (2022) found the best correlation with δ 18 O P using region-wide precipitation. However, for a better understandability, we used the grid-cell-based calculation of the stratiform fraction.…”
Section: Correlation Between δ 18 O P and Stratiform Fractionsupporting
confidence: 71%
“…In fact, we achieved the highest R 2 using a region-wide stratiform fraction (not shown). Similarly, Vargas et al (2022) found the best correlation with δ 18 O P using region- wide precipitation. However, for better understandability, we used the grid-cell-based calculation of the stratiform fraction.…”
Section: 1029/2023jd040630mentioning
confidence: 87%